2021
DOI: 10.1016/j.xpro.2021.100737
|View full text |Cite
|
Sign up to set email alerts
|

Profiling single-cell chromatin accessibility in plants

Abstract: Summary Coupling assay for transposase-accessible chromatin sequencing (ATAC-seq) with microfluidic separation and cellular barcoding has emerged as a powerful approach to investigate chromatin accessibility of individual cells. Here, we define a protocol for constructing single-cell ATAC-seq libraries from maize seedling nuclei and the preliminary computational steps for assessing data quality. This protocol can be readily adapted to other plant species or tissues with minor changes to reveal chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Such developmental trajectories have also been compared between species. Using an optimized protocol (88), a comparison of maize and Arabidopsis TF motif activity across phloem companion cell development revealed highly conserved and innovative TF dynamics (86).…”
Section: Scatac-seqmentioning
confidence: 99%
“…Such developmental trajectories have also been compared between species. Using an optimized protocol (88), a comparison of maize and Arabidopsis TF motif activity across phloem companion cell development revealed highly conserved and innovative TF dynamics (86).…”
Section: Scatac-seqmentioning
confidence: 99%
“…Nuclei purification using flow cytometry: We use a Moflo Astrios EQ running preservative- free flow cytometry solution. The following gating strategy and parameters were modified from Marand et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…We attempted nuclei isolation with several published nuclei isolation protocols (Marand et al 2021; Thibivilliers, Anderson, and Libault 2020; Sikorskaite et al 2013) yet did not recover robust nuclei with our target species. During troubleshooting, we observed that the tissue disruption method, the concentration of detergent, as well as centrifugation and resuspension steps significantly influenced the integrity of isolated nuclei.…”
Section: Introductionmentioning
confidence: 99%